Reliability of a 90nm Embedded Multi-time Programmable Logic NVM Cells Using Work-function Engineered Tunneling Device - Paulsen, Ron (2007 International Reliability Physics Symposium, 2007)
An embedded multi-time programmable (MTP) nonvolatile memory (NVM) has been developed in a standard 90nm logic process. Using a work function engineered tunneling device and 70A tunneling oxide, excellent endurance (>500k cycles) has been achieved. Reliability of the NVM is evaluated against the traditional tunneling device and a model is proposed to explain the observed reliability differences.